KECUKUPAN ASUPAN GIZI REMAJA VEGETARIAN DAN NONVEGETARIAN DI YAYASAN SRI SATHYA SAI BALI TAHUN 2011 - Meliyani, Hildagardis; Adhi, Kadek Tresna; Sutiari, Ketut (ARCHIVE OF COMMUNITY HEALTH; Vol 1 No 1 (2012): Juni (2012)DO - 10.24843/ACH.2012.v01.i01.p07)
Vegetarian diet tends to have nutrient de? ciencies in meat sources nutrient. The aim of this study was to analyze the di? erences in the level of nutrient consumption among teens vegetarian and non-vegetarian. This study was a cross sectional study. The sampling technique uses a consecutive sampling and consisting of 45 vegetarian and 51 nonvegetarian aged between 11-19 years. Food consumption data ware collected by interview using food recall form. The results showed that the level of nutrient consumption (energy, protein, calcium, iron, zinc, and vitamin C) in the majority of vegetarian and non-vegetarian are categorised into the low category. There was no signi? cant di? erence in consumption levels of energy, protein, iron, zinc, and vitamin C among vegetarian and nonvegetarian (p>0,05). In addition, there was no signi? cant di? erence in the level of calcium intake in vegetarians and non-vegetarian (p<0,05).
Keywords: Teenager, Vegetarian, Consumption Level